Determinants of growth and convergence in a growing economy with heterogeneous entrepreneurs - Dirk Dohse; Ingrid Ott (Kiel Institute for the World Economy (IfW), 2008)
We develop an endogenous growth model which is focussed on entrepreneurial skills and their impact on growth and convergence. Our work is closely related to the model by Acemoglu et al. (2006) but extends their analysis in some important respects. Entrepreneurs in our model dispose of two different skills (technological and systemic skills) and we are able to show that it is not only the absolute skill level but also the aggregate distribution of different skills that drives growth and convergence of an economy towards the world technology frontier.
Keywords: O31; O33; O38; J24; L26; 330; Growth; skills; innovation; selection; distance to frontier; Neue Wachstumstheorie; Unternehmer; Qualifikation; Innovation; Entwicklungskonvergenz; Technischer Fortschritt; Theorie